Metabolomic Evaluation of Ralstonia solanacearum Cold Shock Protein Peptide (csp22)-Induced Responses in Solanum lycopersicum - Zeiss, Dylan R.; Steenkamp, Paul A.; Piater, Lizelle A.; Dubery, Ian A. (Frontiers in Plant Science, 2022)
Ralstonia solanacearum, the causal agent of bacterial wilt, is one of the most destructive bacterial plant pathogens. This is linked to its evolutionary adaptation to evade host surveillance during the infection process since many of the pathogen’s associated molecular patterns escape recognition. However, a 22-amino acid sequence of R. solanacearum-derived cold shock protein (csp22) was discovered to elicit an immune response in the Solanaceae. Using untargeted metabolomics, the effects of csp22-elicitation on the metabolome of Solanum lycopersicum leaves were investigated. Additionally, the study set out to discover trends that may suggest that csp22 inoculation bestows enhanced resistance on tomato against bacterial wilt. Results revealed the redirection of metabolism toward the phenylpropanoid pathway and sub-branches thereof. Compared to the host response with live bacteria, csp22 induced a subset of the discriminant metabolites, but also metabolites not induced in response to R. solanacearum. Here, a spectrum of hydroxycinnamic acids (especially ferulic acid), their conjugates and derivatives predominated as signatory biomarkers. From a metabolomics perspective, the results support claims that csp22 pre-treatment of tomato plants elicits increased resistance to R. solanacearum infection and contribute to knowledge on plant immune systems operation at an integrative level. The functional significance of these specialized compounds may thus support a heightened state of defense that can be applied to ward off attacking pathogens or toward priming of defense against future infections.